Neoliberalism in the North American University: Toward Integrating Divisions in Agent Orientation Via a Follettian Differentiated Relational Ontology - M. Pelly, R. Duncan; Boje, David (Communication & Language at Work, 2019)
This paper uses observations from empirical articles and personal experiences of the authors to explore issues associated with the rise of neoliberalism and academic capitalism in the contemporary public university. It frames these issues as stemming from conflicting ontologies between academicians who adhere to the differentiated individual ontology and university administrators who favor the undifferentiated individual ontology. To overcome the disconnect, a differentiated relational ontology that adheres to principles of Mary Parker Follett and Alfred North Whitehead is proposed. The driving force behind this ontology can be highlighted through a communicated crisis, and a specific application of Follett’s differentiated relational ontology is Ensemble Learning Theory (ELT). A potential limitation of this study is generalizability, because the focus is centered on North American public universities and anecdotes are used to characterize a broader educational problem. This evolution is pertinent to academicians and administrators because the ontological impasse experienced in North American public universities threatens their existence as institutions, and has a broader and potentially negative impact on the quality of educational focus and output.